2015
DOI: 10.1080/02134748.2014.991520
|View full text |Cite
|
Sign up to set email alerts
|

Spanish version of the Cultural Intelligence Scale (CQS) / Versión española de la Escala de Inteligencia Cultural (EIC)

Abstract: In recent years, the concept of cultural intelligence has received increasing attention by researchers and professionals because of its theoretical and practical importance. To understand why some individuals adapt more effectively than others to culturally different social contexts has become a goal with implications for education, recruitment and the prevention of social conflict. The goal of this study was to adapt the Cultural Intelligence Scale (CQS) to Spanish. To do so, two studies were carried out. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
4
10
0
Order By: Relevance
“…Furthermore, item loadings on the factors, that they belong to were greater than their loadings on other factors. These results are consistent with previous studies (Al-Dossary, 2016;Ang et al, 2007;Gozzoli & Gazzaroli, 2018;Khan & Hasan, 2016;Moyano et al, 2015;Şahin et al, 2013;Starčević et al, 2017), which is another supportive evidence of the construct validity for CQS with general and four specific factor structure, and the consistency of the relationships between CQS components across different cultures and countries. Moreover, this CTT-based evidence supported the CQS validity established by IRT-GRM in this study, which support relying on CQS full scale as well as subscales in assessing and interpreting CQ.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, item loadings on the factors, that they belong to were greater than their loadings on other factors. These results are consistent with previous studies (Al-Dossary, 2016;Ang et al, 2007;Gozzoli & Gazzaroli, 2018;Khan & Hasan, 2016;Moyano et al, 2015;Şahin et al, 2013;Starčević et al, 2017), which is another supportive evidence of the construct validity for CQS with general and four specific factor structure, and the consistency of the relationships between CQS components across different cultures and countries. Moreover, this CTT-based evidence supported the CQS validity established by IRT-GRM in this study, which support relying on CQS full scale as well as subscales in assessing and interpreting CQ.…”
Section: Discussionsupporting
confidence: 92%
“…Considering the essential role of cultural intelligence in the relationship between openness to experience and job satisfaction, the researcher suggests future studies to adapt the cultural intelligence scale into the Indonesian language. Currently, the cultural intelligence scale has been adapted into three languages: English (Ang et al, 2007), Turkish (Sahin, Gurbuz, Koksal, & Ercan, 2013), and Spanish (Moyano, Tabernero, Melero, & Trujillo, 2015). The idea is based on Muniz, Elosua, and Hambleton (2013( , in Moyano et al, 2015 who recommend other researchers to adapt testing tools into various languages so that the construct can be evaluated in a reliable manner, hence prompting researchers or practitioners who use that language in particular to use the scale.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the cultural intelligence scale has been adapted into three languages: English (Ang et al, 2007), Turkish (Sahin, Gurbuz, Koksal, & Ercan, 2013), and Spanish (Moyano, Tabernero, Melero, & Trujillo, 2015). The idea is based on Muniz, Elosua, and Hambleton (2013( , in Moyano et al, 2015 who recommend other researchers to adapt testing tools into various languages so that the construct can be evaluated in a reliable manner, hence prompting researchers or practitioners who use that language in particular to use the scale. Secondly, job satisfaction is one of the factors to measure the effectiveness of expatriates (Rose et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Ang et al (2007) scale adapted to Spanish by Moyano et al (2015) was used. The scale consists of 20 items that evaluate four factors: (1) the meta-cognitive component (“I am aware of cultural differences and adapt to them in interactions with people from other cultures”; α = 0.72); (2) the cognitive component (“I know the cultural values and religious beliefs of other cultures”; α = 0.87); (3) the motivational component (“I enjoy living in other cultures not familiar to me”; α = 0.83); and (4) the behavioral component (“I alter my facial expression when the cultural interaction situation requires it”; α = 0.84).…”
Section: Methodsmentioning
confidence: 99%
“…This construct represents the capacity to effectively adapt to contexts with a strong cultural component, and it could be considered a protective factor against radicalization and violent extremism (Fang et al, 2018; Trujillo and Moyano, 2018). Although it is a territory that still needs to be explored, Moyano et al (2015) found that cultural intelligence showed a negative relationship with constructs such as the meaning of life and the need for cognitive closure, which, in turn, have been proposed as factors influencing violent extremism (Klein and Kruglanski, 2013; Kruglanski et al, 2015; Trujillo et al, 2016). This leads to the assumption that cultural intelligence could also be acting as a moderator in the process of radicalization so that people with lower levels of cultural intelligence would be more willing to use violence.…”
Section: The Role Of Identity and Culturementioning
confidence: 99%